Ankle Joint Control in People with Chronic Ankle Instability During Run-and-cut Movements - Fuerst, Patrick; Gollhofer, Albert; Lohrer, Heinz; Gehring, Dominic (International Journal of Sports Medicine, 2018)
Despite a considerable amount of research, the deficits causing recurrent sprains in people with chronic ankle instability are still unclear. Changes in frontal plane kinematics and decreased peroneal activation have been proposed as potential underlying mechanisms, but whether people with ankle instability show deficits in control of injury-relevant movements is not well understood. Therefore, the purpose of the present study was to analyse ankle joint kinematics and kinetics as well as neuromuscular activation during dynamic change-of-direction movements. Eighteen participants with functional instability, 18 participants with functional and mechanical instability and 18 healthy controls performed 45° sidestep-cutting and 180° turning movements in reaction to light signals. During sidestep-cutting both instability groups displayed significantly lower inversion angles than controls when the trials with the highest maximum inversion angle of each participant were compared. In turning movements, participants with functional instability presented significantly lower average maximum inversion angles than controls as well as higher peroneal activation before foot strike than participants with both functional and mechanical instability. We theorize that the observed changes in movement kinematics of participants with chronic ankle instability are the result of a protective strategy to limit frontal plane ankle joint loading in potentially harmful situations.
Keywords: ankle injuries; biomechanics; cutting movements